2019
DOI: 10.1093/eurpub/ckz209
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and beliefs on vaccines among a sample of Italian pregnant women: results from the NAVIDAD study

Abstract: Background Vaccine hesitancy is an emerging phenomenon in European countries and leads to decreasing trends in infant vaccine coverage. The aim of this study was to analyze the level of confidence and correct awareness about immunizations, which are crucial for the success of vaccination programmes. Methods As part of the NAVIDAD multicentre study, we examined vaccination confidence and complacency among a sample of 1820 preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The strongest predictors of mandatory vaccination support in our study were increased trust in official healthcare authorities' guidelines and recommendations (such as information on vaccines) and more frequent use of preventive services. Our findings are supported by previous work which found that interaction with healthcare providers and credible health information by trustworthy and reliable sources were commonly associated with acceptance and uptake of recommended vaccinations 16,18,20,21,24,26,31,32 . In fact, a review of the literature highlighted that the credibility of institutions might influence vaccination attitudes more than information 32 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The strongest predictors of mandatory vaccination support in our study were increased trust in official healthcare authorities' guidelines and recommendations (such as information on vaccines) and more frequent use of preventive services. Our findings are supported by previous work which found that interaction with healthcare providers and credible health information by trustworthy and reliable sources were commonly associated with acceptance and uptake of recommended vaccinations 16,18,20,21,24,26,31,32 . In fact, a review of the literature highlighted that the credibility of institutions might influence vaccination attitudes more than information 32 …”
Section: Discussionsupporting
confidence: 89%
“…The most common source of vaccine information are healthcare providers, and health information credibility stemming from trustworthy providers as well as frequent interaction with the healthcare system was found to positively influence vaccination uptake 16,20,21,24,25 . In recent years the Internet has emerged as an important source of information on vaccines as well.…”
Section: Introductionmentioning
confidence: 99%
“…These results are probably due to their deep knowledge about the impact of these diseases on pregnant women and newborns. A broad sentiment of vaccine hesitancy has grown throughout Europe [ 12 , 35 ] over the last decade. This sentiment is present also among HCWs [ 36 , 37 ], highlighting the lack of confidence in vaccine safety and usefulness.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the perception of the diseases' danger, we found that this is significantly related to the quality of the information sources. A similar analysis has been conducted and it has shown that the sources of information influence the level of knowledge of the pregnant women [19].…”
Section: Discussionmentioning
confidence: 89%
“…A cross-sectional multicentre study (NAVIDAD study) examined the determinants of acceptance of mandatory vaccine restoration, identifying one of the main factors in information sources [18]. A subsequent analysis from the same working group focused on awareness and confidence in immunization [19]. In the context of the Navidad study, we analysed the use of information sources by pregnant women in the province of Ferrara.…”
Section: Introductionmentioning
confidence: 99%